POLITICS OF DEVELOPMENT IN LOCAL ECONOMIC GROWTH: A CASE OF JHARKHAND: DEVELOPMENT, GOVERNANCE AND GOVERNMENT, DEMOGRAPHIC PROFILE OF STATE, CNT & SPT ACT AND POLITICS OF DEVELOPMENT, - Afroz, Dr Md; ALAM, MD TABREZ (IJRDO - Journal of Social Science and Humanities Research, 2019)
India is considered one of the fastest growing economies in contemporary times among developing countries in the world because of its historical legacies of commercial and cultural wealth of past. Despite being a newly industrializing nation, it continues to face the challenges of attributes of developing countries like; poverty, illiteracy, poor health services and discursive politics. Jharkhand being the 28th state of India has been separated 17th years ago from Bihar on the pretext of regional development that had been neglected since long. The tribal state has huge natural resources that attracted many business houses to set-up industries. The contemporary CNT Act 1908 and SPT Act 1949 has become hotly contested topic in local politics. There is huge stake of politics in development in local economic growth. The negative political trend has become hurdles affecting the prospects for positive growth in Jharkhand. This paper tries to study the causal effects of pervasive politics on recent government initiatives to amend the CNT and SPT Acts to ease the land transfer for industrial development in Jharkhand. It tries to understand why political parties persistent on amending these two bills which has been brought to protect the tribal land & properties. The study conduct on the basis of primary data from the field and secondary data has been collected from various reports and newspapers.